2018
DOI: 10.30773/pi.2018.02.25.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atomoxetine on Height and Weight in Korean Children and Adolescents with Attention-Deficit/Hyperactivity Disorder: A Retrospective Chart Review

Abstract: Objective We aimed to investigate the long-term effects of atomoxetine on growth in Korean children and adolescents with attention-deficit/hyperactivity disorder (ADHD). Methods The medical records of 82 subjects (mean age, 9.0±2.0 years; 64 boys) with ADHD treated with atomoxetine for at least 1 year at the Department of Psychiatry at Asan Medical Center were retrospectively reviewed. Height and weight data were prospectively obtained and retrospectively gathered and converted to age- and gender-corrected z s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…There was a significant effect between only boys and differences in height-SDS z-scores and weight-SDS z-scores between baseline and follow-up, but in the regression analysis, gender did not have an effect on predicted difference and final anthropometric values. Our results were coherent with the findings of the study by Kweon et al [22] which did not find interaction between boys and girls in the effect of Atx on growth [22]. Also Biederman et al [25] showed the effect of emotional disorders on z-scores which are greater weight in girls and with smaller height in boys [25].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There was a significant effect between only boys and differences in height-SDS z-scores and weight-SDS z-scores between baseline and follow-up, but in the regression analysis, gender did not have an effect on predicted difference and final anthropometric values. Our results were coherent with the findings of the study by Kweon et al [22] which did not find interaction between boys and girls in the effect of Atx on growth [22]. Also Biederman et al [25] showed the effect of emotional disorders on z-scores which are greater weight in girls and with smaller height in boys [25].…”
Section: Discussionsupporting
confidence: 92%
“…It is unclear if and in what dimension comorbidities have an influence on weight problems in examined patients with ADHD. A significant decline between baseline and followup weight and the significant decrease in the z-score for height were observed in the total sample, but the decline was not observed in all subgroups supporting the current literature that has evaluated the clinical importance of reduced parameters [22]. Several mechanisms explain the reason of Atx on height and weight.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Methylphenidate is a short-acting stimulant that is well tolerated in the short term. It reduces height and weight in the long term [ 10 , 11 ], while the short-term effects of atomoxetine on growth development are not well documented. Long-term atomoxetine treatment may be associated with deficits in height growth [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It reduces height and weight in the long term [ 10 , 11 ], while the short-term effects of atomoxetine on growth development are not well documented. Long-term atomoxetine treatment may be associated with deficits in height growth [ 10 ]. In addition, some studies have indicated that atomoxetine might have additional side effects beyond norepinephrine reuptake inhibition.…”
Section: Introductionmentioning
confidence: 99%